Measurement of grounding system resistance based on ground high frequency behavior for different soil type - Jambak, M. ‘Irfan (2000)
Reliable and accurate measurement of ground resistance value (GRV) is of utmost important for an effective lightning protection system (LPS). However, common and conventional ground resistance measurement using DC current injection does not provide the true value of resistance when considering the natural characteristic of lightning current. When the LPS conducts naturally occurring lightning surges to ground, the ground resistance behaves like an impedance. Practically the impedance of the grounding system is much higher than the DC ground resistance. Because of this, measuring GRV using DC or fixed frequency current is not highly accurate. This is so because the impedance takes account of the surge high frequency response. This paper describes a new technique that can determine the true ground resistance value more accurately in a noisy environment using an R-L-C resonance circuit concept